A class of novel 2T2R and 3T2R parallel mechanisms with large decoupled output rotational angles. (August 2017) - Jin, Xiaodong; Fang, Yuefa; Qu, Haibo; Guo, Sheng
Abstract: This article focuses on the synthesis and analysis of a class of novel 2T2R (T denotes Translation and R denotes Rotation) and 3T2R parallel mechanisms (PMs) with large decoupled output rotational angles. Two articulated moving platforms (AMPs) composed by revolute joints are proposed. A common parallelogram and an evolution parallelogram which are used to orient the rotation axes of the AMPs are designed and analyzed. By means of Lie group theory, the limbs connected in the AMPs are enumerated and two types of 2T2R PMs are synthesized. Then, based on the proposed 2T2R PMs, a family of 3T2R PMs are obtained through adding a translational degree of freedom (DOF). The fact that the orthogonal arrangement of the revolute joints in the AMPs eliminates the interference between the two rotations guarantees the high rotational performance of the manipulators. Finally, the inverse kinematics of the example PM is conducted and the workspace is obtained to illustrate the high rotational capability.